Arginine-Silicate-Inositol Promotes Femoral Fracture Healing in Rats - Demir, Sukru; Şahin, Kazım; Ozercan, Ibrahim Hanifi; Once, Gokhan; Key, Sefa; Gurger, Murat (Springernature, 2026)
The arginine-silicate-inositol (ASI) complex (Arg 49.47%, silicon 8.2%, inositol 25%) is a bioavailable source of silicon and arginine with potential benefits for bone metabolism. This study aimed to investigate the effects of oral ASI supple-mentation on fracture healing in a rat femoral fracture model. Twenty-eight female Wistar-Albino rats were subjected to standardized femoral osteotomy using a multiple drilling technique under anesthesia. Group 1 and Group 2 received a standard diet for 8 weeks, Group 3 received low-dose ASI, and Group 4 received high-dose ASI. Histopathological analy-sis demonstrated a significant increase in osteoblast numbers in ASI-treated groups, with the highest values observed in the high-dose ASI group (p < 0.001). Osteoclast numbers were significantly reduced in the high-dose ASI group compared with controls (p = 0.017). Radiological evaluation revealed the absence of union in fracture controls, whereas low-dose ASI promoted fracture union with normal callus formation, whereas high-dose ASI resulted in more extensive and mature callus formation. In conclusion, ASI supplementation significantly enhanced fracture healing, callus maturation, and new bone formation in a dose-dependent manner. These findings suggest that ASI may be a promising nutritional strategy for supporting bone repair.
Keywords: Arginine-silicate-inositol complex; Fracture healing